REVIEW ON THE IMPORTANCE OF TRANSPARENCY IN INTERNATIONAL TRADE BASED ON THE RULES OF THE WORLD TRADE ORGANIZATION - Jessica Callista; Rahmat Dwi Putranto (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2022)
This study aims to obtain information and analyze the rules of the World Trade Organization (WTO) regarding the importance of transparency in international trade between WTO member countries, where supporting information and data are needed in the sustainability of trade transactions. In international trade between WTO member countries, there are various economic, political and social backgrounds from developed countries (developed countries), developing countries (developing countries), and less developed (least-developed countries). This background encourages the strengthening of transparency in trade in goods and services through a mechanism that is agreed upon and implemented jointly, so that it is expected that each WTO member country can provide and obtain reliable and up-to-date information and supporting data. The transparency mechanism has the main objective of providing smooth trade in goods and services and reducing obstacles related to obtaining the required information and data. However, in implementing transparency, WTO member countries are also often faced with challenges, such as in the case of the global crisis of the COVID-19 pandemic whose impact has been felt by all WTO member countries. All stakeholders, starting from the government, employers, workers, and so on, need to work together in carrying out compliance with the transparency mechanism as stipulated in the WTO rules to realize smooth international trade.